Rebubbling rate in preloaded versus surgeon prepared DSAEK. Issue 2 (March 2022) - Pagano, Luca; Gadhvi, Kunal A; Coco, Giulia; Fenech, Matthew; Titley, Mitchell; Levis, Hannah J; Ruzza, Alessandro; Ferrari, Stefano; Kaye, Stephen B.; Parekh, Mohit; Romano, Vito
Purpose: To compare the clinical outcomes of eye bank preloaded Descemet stripping automated endothelial keratoplasty (DSAEK) grafts and surgeon prepared. Methods: In this retrospective study, the data were obtained from two groups (a) surgeon cut DSAEK where tissue was prepared by the surgeon immediately before surgery, and (b) preloaded DSAEK tissue shipped to the surgeon after preparation by the eye bank. Standard DSAEK preparations using Moria microkeratome with single pass method were performed. For the tissues prepared by the eye banks, they were preloaded in an iGlide device and shipped in transport media. Standard DSAEK surgery using bimanual pull-through technique was performed for all the grafts. Air was used as a tamponade. Main outcome measures included best corrected visual acuity (BCVA) and rebubbling rate. Result: Out of 107 eyes of 101 patients that underwent DSAEK surgery, 33 tissues were prepared by the surgeon (sc-DSAEK), while 74 were prepared by the eye bank (pl-DSAEK). sc-DSAEK showed a rebubbling rate of 9.1%, compared to the 16.2% for the preloaded DSAEK ( p  = 0.11). There was no statistical difference in postoperative BCVA between the two groups. Logistic regression analysis showed no association between detachment rate and cataract surgery, graft preparation method, graft diameter and reason for graft. Conclusion: Preloaded grafts have similar rebubbling rate and visual acuity achieved compared with surgeon prepared grafts.